Spectrum requirements for the future development of IMT-2000 and systems beyond IMT-2000 - Yoon, Hyun-Goo; Chung, Woo-Ghee; Jo, Han-Shin; Lim, Jaewoo; Yook, Jong-Gwan; Park, Han-Kyu (Journal of communications and networks, 2006)
In this paper, the algorithm of a methodology for the calculation of spectrum requirements was implemented. As well, the influence of traffic distribution ratio among radio access technology groups, spectral efficiency, and flexible spectrum usage (FSU) margin was analyzed in terms of the spectrum requirements, with a view toward for future development of international mobile telecommunication (IMT)-2000 and systems beyond IMT-2000. The calculated spectrum requirement in the maximum spectral efficiency case is reduced by approximately 40% compared to a minimum spectral efficiency case. The effect of the distribution ratio on the required spectrum is smaller than the effect of the spectral efficiency. As the flexible spectrum usage margin increases by 1.0 dB, the total spectrum requirement decreases by 0.9 dB. The required spectrum for the market input parameter, ρ= 0.5 is 801.63 MHz, while the required spectrum for ρ= 1.0 is 6295.4 MHz. This is equivalent to an increase of 785.32%.